UTILIZING SONGS TO ENHANCE ENGLISH LEARNING FOR YOUNG MINDS - Abdikarimova Gulayim Baxtiyar qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Incorporating songs into English language instruction for young learners enhances engagement, facilitates vocabulary acquisition, promotes pronunciation refinement, deepens grammatical comprehension, strengthens mnemonic retention, and fosters cultural insights. By integrating music into language learning activities, educators can create dynamic and immersive learning experiences that empower young learners to thrive in their linguistic journey and become proficient communicators in English.